Paenibacillus polymyxa A26 Sfp-type PPTase inactivation limits bacterial antagonism against Fusarium graminearum but not of F. culmorum in kernel assay - Abd El Daim, Islam A.; Häggblom, Per; Karlsson, Magnus; Stenström, Elna; Timmusk, Salme (Frontiers in Plant Science, 2015)
Fusarium graminearum and F. culmorum are the causing agents of a destructive disease known as Fusarium head blight (FHB). FHB is a re-emerging disease in small grain cereals which impairs both the grain yield and the quality. Most serious consequence is the contamination of grain with Fusarium mycotoxins that are severe threat to humans and animals. Biological control has been suggested as one of the integrated management strategies to control FHB. Paenibacillus polymyxa is considered as a promising biocontrol agent due to its unique antibiotic spectrum. In order to optimize strain A26 production, formulation and application strategies traits important for its compatibility need to be revealed. Here we developed a toolbox comprising of dual culture plate assays and wheat kernel assays including simultaneous monitoring of FHB causing pathogens A26 and mycotoxins produced. Using this system we show that, besides generally known lipopeptide antibiotic production by P. polymyxa, biofilm formation ability may play a crucial role in the case of stain A26 F. culmorum antagonism.